2020
DOI: 10.1155/2020/9485398
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin Downregulates Cyclooxygenase‐2 Expression and HIF‐1α/VEGF Signaling‐Related Angiogenesis in a Mouse Model of Abdominal Aortic Aneurysm

Abstract: Objective. Abdominal aortic aneurysm (AAA) development has been characterized by increased expression of vascular endothelial growth factor (VEGF), which contributes to angiogenesis via cyclooxygenase-2 (COX-2). Quercetin, one of the most common and well-researched flavonoids and abundant in vegetables and fruits, has beneficial effects in inhibiting angiogenesis. This study investigated the antiangiogenic effects of quercetin on experimental aneurysms. Methods. We utilized the in vivo AAA mouse model induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 40 publications
1
15
0
Order By: Relevance
“…In several cancers models, such as prostate and breast cancer, Qu has been associated in mediating several angiogenesis pathways, including the Vascular Endothelial Growth Factor Receptor-2 mediated pathway of angiogenesis, repressing the downstream-regulatory target AkT expression; thus, restraining and restricting growth of the tumor [ 80 , 85 ].Lian Wang et al, through a mice model study, stated that Qu, as an angiogenesis inhibitor, reduces neovascularization growth, which is mediated via the inhibition of cyclooxygenase-2 (COX-2) [ 86 ]. It also decreases the expression of proangiogenic mediators, including VEGF-A, and Hypoxia-inducible factor 1-alpha; thus, preventing metastasis of cancer cells [ 87 , 88 ].…”
Section: Major Mechanism Of Qu In Management Of Cancermentioning
confidence: 99%
“…In several cancers models, such as prostate and breast cancer, Qu has been associated in mediating several angiogenesis pathways, including the Vascular Endothelial Growth Factor Receptor-2 mediated pathway of angiogenesis, repressing the downstream-regulatory target AkT expression; thus, restraining and restricting growth of the tumor [ 80 , 85 ].Lian Wang et al, through a mice model study, stated that Qu, as an angiogenesis inhibitor, reduces neovascularization growth, which is mediated via the inhibition of cyclooxygenase-2 (COX-2) [ 86 ]. It also decreases the expression of proangiogenic mediators, including VEGF-A, and Hypoxia-inducible factor 1-alpha; thus, preventing metastasis of cancer cells [ 87 , 88 ].…”
Section: Major Mechanism Of Qu In Management Of Cancermentioning
confidence: 99%
“…Quercetin, a flavonoid with anti-inflammatory activity, was the most abundant ingredients that could act on AAA and inhibited the development of AAA in mice (Wang et al, 2012). Additionally, quercetin attenuated neovascularization during AAA growth (Wang et al, 2020) and decreased oxidative stress in AAA mouse models (WANG et al, 2014). Luteolin inhibited vascular smooth muscle cells proliferation and migration (Xu et al, 2015;Wu et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Related to this study, the treatment of murine AAAs with resveratrol, a polyphenol, resulted in decreased AAA formation and elevated phox-p47 levels [ 123 ]. In separate studies, Quercetin, a polyphenol and antioxidant, also demonstrated decreased AAA formation and decreased HIF-1α and VEGF signaling in experimental AAAs [ 124 ]. These studies using Quercetin also treated with Celecoxib, a known anti-inflammatory, separately as a positive control to confirm the ability to attenuate AAA formation.…”
Section: Influence Of Pharmacologic Nadph Oxidases In Experimental Aaasmentioning
confidence: 99%